SISTEM INFORMASI ALUMNI PROGRAM STUDI TEKNIK INFORMATIKA STMIK NURDIN HAMZAH BERBASIS WEB: ALUMNAE, INFORMATICS ENGINEERING, WEB, PHP, MYSQL - Puspitorini, Sukma; Al Amin; Purnama, Fery (LP2M STMIK Nurdin Hamzah Jambi, 2017)
Informatics Engineering is one of the department  at STMIK Nurdin Hamzah, Jambi which was opened since 2002. According to data from the academic division STMIK Nurdin Hamzah, until 2012, Prodi Informatics Engineering has graduated 735 colleger. However, the alumni data processing has not been done optimally. The purpose of this research is to make alumni website to facilitate the alumni of Informatics Engineering Department to tie the ropes of brotherhood and sharing information and job vacancy after graduated.  This system is done by design that includes database design and interface. Programming language used to create web-based applications, while to create a website using PHP programming language and using MySQL as database.